2020
DOI: 10.1126/sciadv.aaz3050
|View full text |Cite
|
Sign up to set email alerts
|

Actin modulates shape and mechanics of tubular membranes

Abstract: The actin cytoskeleton shapes cells and also organizes internal membranous compartments. In particular, it interacts with membranes for intracellular transport of material in mammalian cells, yeast, or plant cells. Tubular membrane intermediates, pulled along microtubule tracks, are formed during this process and destabilize into vesicles. While the role of actin in tubule destabilization through scission is suggested, literature also provides examples of actin-mediated stabilization of membranous structures. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
(52 reference statements)
1
13
0
Order By: Relevance
“…However, in spine-extending regions, the orientation changed rapidly along the extending direction. Studies showed that the actin cytoskeleton interacted with plasma membrane changes the morphology 54 . OLID-SDOM techniques may even drive forward the studies of synaptic activity regarding to the dynamics of dendritic spine morphology plasticity.…”
Section: Resultsmentioning
confidence: 99%
“…However, in spine-extending regions, the orientation changed rapidly along the extending direction. Studies showed that the actin cytoskeleton interacted with plasma membrane changes the morphology 54 . OLID-SDOM techniques may even drive forward the studies of synaptic activity regarding to the dynamics of dendritic spine morphology plasticity.…”
Section: Resultsmentioning
confidence: 99%
“…The bottom term πηr bead catches the thermal fluctuations of the isolated bead in the surrounding viscous medium while the upper term expresses the damping of nanotube fluctuations due to the viscosity η I inside the nanotube. Here, an actin sleeve of a few hundred nanometers surrounds the membrane nanotube [22]. We propose that this sleeve affects the membrane nanotube peristaltic modes by increasing the viscosity around the nanotube.…”
Section: Fluctuations Of Actin-covered Membrane Nanotubesmentioning
confidence: 93%
“…Under our conditions, tension ranges between 0.2 and 50 × 10 −6 N/m (Fig. 2), while aspirating liposomes in a micropipet gives 10-200 × 10 −6 N/m [14,22]. The detailed effect of membrane tension is assessed in Sec.…”
Section: A Experimental Assaymentioning
confidence: 97%
See 2 more Smart Citations